Within but without: human rights and access to HIV prevention and treatment for internal migrants - Amon Joseph J; Todrys Katherine (BMC, 2009)
Abstract Worldwide, far more people migrate within than across borders, and although internal migrants do not risk a loss of citizenship, they frequently confront significant social, financial and health consequences, as well as a loss of rights. The recent global financial crisis has exacerbated the vulnerability internal migrants face in realizing their rights to health care generally and to antiretroviral therapy in particular. For example, in countries such as China and Russia, internal migrants who lack official residence status are often ineligible to receive public health services and may be increasingly unable to afford private care. In India, internal migrants face substantial logistical, cultural and linguistic barriers to HIV prevention and care, and have difficulty accessing treatment when returning to poorly served rural areas. Resulting interruptions in HIV services may lead to a wide range of negative consequences, including: individual vulnerability to infection and risk of death; an undermining of state efforts to curb the HIV epidemic and provide universal access to treatment; and the emergence of drug-resistant disease strains. International human rights law guarantees individuals lawfully within a territory the right to free movement within the borders of that state. This guarantee, combined with the right to the highest attainable standard of health set out in international human rights treaties, and the fundamental principle of non-discrimination, creates a duty on states to provide a core minimum of health care services to internal migrants on a non-discriminatory basis. Targeted HIV prevention programs and the elimination of restrictive residence-based eligibility criteria for access to health services are necessary to ensure that internal migrants are able to realize their equal rights to HIV prevention and treatment.